(untitled) (Research, Society and Development, 2022)
Larviculture is a critical period in the production of ornamental fish, due to the productive and nutritional needs of the larvae in the first days of life. The supply of live food is essential for the survival of the larvae, being Artemia sp. the most used food, although it represents a high cost. Making it necessary to search for lower cost live foods such as the nematode microworm. The present work was developed with the objective of evaluating, by means of growth, development and survival indices, the microverminal supply exclusively or associated to artemia and plankton for Betta splendens larvae. Larvae fed with microworm and artemia showed higher final weight, final length, length gain, higher rate of specific development and survival. The rate of uniformity in the treatment that received only microverm did not differ from the other treatments, however, the larvae submitted to the microworm and artemia diet showed a better uniformity rate when compared to those fed with microverm and plankton. The feeding strategy aimed at supplying microverm and artemia together promoted the best growth, development and survival rates in the initial Betta splendens larviculture.